Uji Efek Teratogenik dari Yoghurt Terhadap Fetus Mencit Putih (Mus musculus) - Dwisari Dillasamola; Almahdy A; Amirah Desri; Skunda Diliarosta (Jurnal Sains Farmasi & Klinis, 2018)
Yogurt is one of the dairy products made from lactic acid fermentation by using Lactobacillus bulgaricus and Streptococcus thermophilus. A study on teratogenic effects of yogurt on the white female mice fetus (Mus musculus) has been carried out. Pregnant mice used were 20 which divided into 4 groups : the control group, D1, D2, and D3. The treatments giveThe mice were Distidelled water (control), 0.52 yogurt (D1), 1.04  yogurt (D2), and 2.08 g yogurt (D3). Data were analyzed using one-way ANOVA followed by Duncan multiple range test. Results showed that administration of yogurt during pregnancy could affect mother body weight of mice (P < 0,05).The administration of yogurt during pregnancy did not affect the number of fetuses and fetal body weight significantly (P > 0,05). Observations with Alizarin solution did not show skeletal defects in comparison to the control group. Observations with Bouin’s solution showed defective visceral cleft palate in fetal mice yogurt group D3. This study conclude that yogurt is safe to consume in groups D1 and D2. Yogurt has the potential to cause fetal teratogenic in group D3